Do Audit Fees Adjust Quickly?—Evidence from India. Issue 5 (October 2021) - Biswas, Shreya
Abstract: The article empirically analyses the partial adjustment in audit fees for top 500 National Stock Exchange-listed firms in India during 2004–2015. The findings indicate that firm characteristics have low explanatory power in predicting year-on-year changes in audit fees in accordance with sticky price literature in economics. We also find evidence of stickiness in audit prices with respect to changes in firm size which is in line with the signalling and credence good theories. The downward stickiness in audit fee may indicate overcharging in the market. However, audit fee stickiness ceases to exist for the set of group firms, highlighting the importance of ownership structure in affecting firm outcomes in India. Recognizing stickiness is important for managers, as it has implications for the audit fee negotiation process.